1957
DOI: 10.1677/joe.0.0150056
|View full text |Cite
|
Sign up to set email alerts
|

The Destructive Effect of Cadmium Ion on Testicular Tissue and Its Prevention by Zinc

Abstract: SUMMARY The subcutaneous administration of cadmium salts (cadmium chloride or lactate) to male rats and mice leads to acute destruction of the testes, with destruction of the seminiferous epithelium and interstitial tissue. These changes in turn evoke castration phenomena, but the atrophied accessory sex organs retain the ability to react to testosterone propionate. Within 20 days after the injection of cadmium, proliferation of fibroblasts in the interstitial spaces under the albuginea begins … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
78
0
3

Year Published

1964
1964
2005
2005

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 358 publications
(84 citation statements)
references
References 3 publications
3
78
0
3
Order By: Relevance
“…It is known that Cd-induced testicular necrosis is common across all animal species having testes: rodents, opossum, armadillos, frogs, pigeons, roosters, and fish (12)(13)(14)(15)(16)(17). Cellular events that precede Cd-induced testicular toxicity indicate that vascular endothelial cell injury is the earliest and, perhaps, the causative event (16,(18)(19)(20)(21)(22)(23)(24).…”
mentioning
confidence: 99%
“…It is known that Cd-induced testicular necrosis is common across all animal species having testes: rodents, opossum, armadillos, frogs, pigeons, roosters, and fish (12)(13)(14)(15)(16)(17). Cellular events that precede Cd-induced testicular toxicity indicate that vascular endothelial cell injury is the earliest and, perhaps, the causative event (16,(18)(19)(20)(21)(22)(23)(24).…”
mentioning
confidence: 99%
“…The ability of zinc to prevent cadmium injury, apparently by a competitive mechanism, was noted by Parizek (1957) and confirmed by others. Cysteine and other thiols also protect the testis from cadmium, as does prior administra¬ tion of a sub-threshold dose of Cd 2 days before the threshold dose.…”
Section: Introductionmentioning
confidence: 59%
“…Cadmium is known to cause selective injury to the testes following injection of a single subacute dose into animals with scrotal testes (Parizek, 1957). Rats treated with as little as 0-012 mmol Cd/kg develop haemorrhagic necrosis of the testes within 48 hr, followed by atrophy and permanent sterility (Gunn & Gould, 1970).…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that these acids are, in fact, the active metabolites (11,18) and that the injury observed is a result of zinc loss from testis, which occurs 4 days after treatment with EGME or methoxyacetic acid (18). Zinc concentration has been shown to have an important role in testicular injury induced by cadmium (19), and phthalate esters (20)(21)(22)). …”
Section: Discussionmentioning
confidence: 99%